Penerapan Teknologi Tepat Guna dan Diversifikasi Pangan pada UKM Olahan Ikan Bandeng di Desa Bulu Cindea Kecamatan Bungoro, Pangkep - Nur Fitriani Usdyana Attahmid; Rahmawati Saleh; Muhammad Yusuf (Jurnal Pengabdian Pada Masyarakat, 2019)
APPLYING APPROPRIATE TECHNOLOGY AND FOOD DIVERSIFICATION IN SMALL AND MEDIUM ENTERPRISES OF MILKFISH PROCESSING IN BULU CINDEA VILLAGE, BUNGORO DISTRICT, PANGKEP. Village of Bulu Cindea Bungoro District is a village located in Pangkep Regency. The village has the potential in developing milk fish based processed food products. The abundance of milkfish products in this area has a positive impact on the Small and Medium Enterprises in the milk processing industry. Milkfish is very popular with the community because it has a low price and has a specific taste. Every 100 grams of fresh milkfish contains: 129 kcal energy, 76.85% water content, 20.38 gram fat content, 20.38 mg protein content, 150 mg phosphorus content, 2 mg iron, vitamin A l50 SI, vitamin B1 : 0.05 mg, and also contains Omega-3 of 14.2%. Milkfish has weaknesses, namely the presence of many thorn bones scattered throughout the meat section and the diversification of processed products is still simple with low product quality, packaging that is not hygenic, packaging identity that includes labeling and nutritional chemical composition has not been met and inadequate business licensing. Empowerment of Micro, Small and Medium Enterprises is the key to the development of small industries in Pangkep Regency, both in terms of quality and quantity, as well as its supporting factors. Through the Community Partnership Program activities, a number of activities to develop fresh milkfish processing business without thorns and shredded fish to Small and Medium Enterprises who are partners are UKM Alifa Mandiri, which is one of the platforms to empower food processing industry players. This activity is very important considering the diversification of processed milkfish processing technology without thorns and shredded fish is still done conventionally so that it requires appropriate technology and diversification of appropriate processing.